Determinan Anemia Pada Ibu Hamil: Literatur Review - Saida, Saida (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Pregnancy-related anemia is a global health issue that can have serious implications for both maternal and fetal health. Anemia during pregnancy is caused by various factors, including iron, folate, and vitamin B12 deficiencies, as well as underlying socioeconomic conditions and infections. The high prevalence of anemia, particularly in developing countries, requires serious attention in efforts to prevent and manage anemia in pregnant women. This literature review was conducted by identifying and analyzing relevant articles on the prevalence, risk factors, management, and impact of anemia during pregnancy. Articles were searched in databases such as PubMed, Google Scholar, and Scopus, using keywords like "Anemia in pregnancy," "Iron deficiency anemia," and "Pregnancy complications." Inclusion criteria included articles published in the last five years, focusing on studies relevant to anemia in pregnant women. Based on the review findings, the prevalence of anemia during pregnancy ranged from 25-45%, with iron deficiency as the primary cause of anemia. Other risk factors included multiple pregnancies, parasitic infections, and low socioeconomic status. Iron, folate, and vitamin B12 supplementation were shown to be effective in increasing hemoglobin levels and reducing anemia prevalence. However, factors such as access to healthcare and adherence to supplementation programs play a critical role in the success of anemia management. Anemia in pregnant women is a complex health issue that requires a multidimensional approach. Public health programs involving nutritional education, supplementation, and routine monitoring are essential to reduce anemia prevalence in pregnant women